Intestinal lymphatic HDL miR‐223 and ApoA‐I are reduced during insulin resistance and restored with niacin. Issue 3 (3rd January 2018) - Mangat, Rabban; Borthwick, Faye; Haase, Tina; Jacome, Miriam; Nelson, Randy; Kontush, Anatol; Vine, Donna F.; Proctor, Spencer D.
Abstract : The intestine is involved in whole‐body lipid and cholesterol homeostasis and secretes lipoproteins containing apolipoprotein (Apo)B48 and discrete ApoA‐I into the mesenteric lymph. The lymphatic system has been proposed to have a significant role in the reverse cholesterol transport pathway associated with HDL‐ApoA‐I. In conditions of insulin resistance (IR), there is intestinal overproduction of chylomicrons containing ApoB48; how‐ ever, there is limited data on the intestinal synthesis and secretion of HDL‐ApoA‐I. microRNA (miR)‐223 has been shown to regulate peripheral HDL metabolism and may impact intestinal‐derived HDL. Niacin (nicotinic acid; vitamin B3) is known to regulate lipid metabolism, but the role of niacin in modulating intestinal lipid and lipoprotein (ApoB48 and ApoA‐I) metabolism is unknown. The aim of this study was to determine the secretion of intestinal lymphatic HDL‐ApoA‐I and the effect of dietary intervention with niacin on these pathways in a rodent model of IR. HDL was isolated from intestinal mesenteric lymph by density ultracentrifugation, and subsequent HDL miR analysis was developed in collaboration with Exiqon Services. Insulin‐resistant rodents were fed chow or chow with niacin (1% w/w) for 6 wk. Intestinal lymph HDL‐ApoA‐I and miR‐223 expression were lower by atleast 45 and 60%, respectively, and lymph HDL was associated with 85% higher triglyceride (TG) content in IR compared to non‐IR control group. Niacin was found to increase secretion of lymph HDL and miR‐223 by at least 50‐60% and to deplete the TGs associated with HDL compared with the nontreated IR group. Niacin significantly increased peroxisome proliferator‐activating nuclear receptor a and carnitine palmitoyltransferase I a mRNA and annulled Tnf‐ α mRNA expression in intestinal (jejunal) explants. Altered intestinal lymphatic HDL‐ApoA‐I and miR‐223 metabolism in IR and modulation by niacin may provide insight into the intestinal‐mediated regulation of the reverse cholesterol transport pathway.—Mangat, R., Borthwick, F., Haase, T., Jacome, M., Nelson, R., Kontush, A., Vine, D. F., Proctor, S. D. Intestinal lymphatic HDL miR‐223 and ApoA‐I are reduced during insulin resistance and restored with niacin. FASEB J. 32, 1602‐1612 (2018). www.fasebj.org